Lingual Artery as the Recipient Vessel of Choice in Patients Requiring a Second or Third Free Flap in Recurrent Oral Cancers and Vessel-Depleted Neck: A 5-Year Experience in a Single Institute - Dhondge, Rajendra; Hussain, Mohsina; Singh, Archana; Nagarkar, Raj (Indian Journal of Plastic Surgery, 2023)
Introduction Reconstruction with free flaps becomes a challenge in recurrent cases having previously treated necks, in patients who have received prior radiation therapy or chemotherapy or both, and where the patient has already undergone free flap reconstruction in a prior surgery. Depleted cervical recipient vessels can increase the complexity of reconstruction in achieving successful free flap prefusion and thereby increasing flap thrombosis and eventually failure.Materials and Methods Over a period of 5 years from January 2018 to February 2023, we encountered a total of 22 cases of recurrent or second primary oral cancer with bilateral necks operated, postadjuvant chemo-radiotherapy, and requiring a second or third free flap reconstruction. In most of the cases we resorted to the lingual artery as the recipient artery of choice.Results No flap loss was reported. No cases were reexplored either for hematoma or for congestion. All patients recovered uneventfully.Conclusion To the best of our knowledge, there has been no paper yet that focuses on the lingual artery to be the recipient vessel of choice in recurrent oral cancers. We find the lingual artery to be a reliable and safe option and advocate its usage as recipient vessel of choice in recurrent oral cancers requiring more than one free flap reconstruction.
Keywords: lingual artery; recipient vessels; free flap; recurrent oral cancer; vessel depleted neck